Research and application of natural air-cooled traction transformer for EMU - JIN Jun (机车电传动)
The safe, efficient, environmentally-friendly, and economically-efficient development of the rail transit industry imposes increasingly demanding requirements on on-board equipment. This study comprehensively analyzed the research directions for traction transformers and the principles and characteristics of natural air cooling technology. The analysis revealed the superior application advantages and economic benefits of natural air-cooled traction transformers compared to traditional forced air-cooled designs. Through systematic research on key technologies, such as the complex flow field distribution of natural air, matching mechanisms for natural air cooling, designs for high impedance and low loss, and algorithms for multi-dimensional line transient temperature rise, a natural air-cooled traction transformer for EMUs was designed and implemented as the first of its kind in China. The relevant key technologies and the comprehensive performance of the product were verified through on-site practical applications. Verification results show that, compared with traditional forced air-cooled traction transformers for EMUs, this new natural air-cooled traction transformer achieves a 2% improvement in efficiency, a 50% reduction in losses, a decrease in noise levels by 15 dB(A), a reduction of approximately 90% in the maintenance workload for the cooling system, and a decrease in total lifecycle costs of about 40%. The research and application outcomes of this product platform and technology provide a more efficient, environmentally-friendly, and cost-effective innovative solution for the development of rail transit.